Method for solid-state regeneration of Al-Cu-based alloy by using AA6063 aluminum skimmings
By plating copper plating on the surface of aluminum dandruff and combined with thermal extrusion and T6 heat treatment process, the problem of the impact of metallurgy combination in aluminum alloy solid regeneration in solid-state regeneration has achieved the preparation of the AL-CU-CU consecutive AL-CU-CU-based alloy with significant improvement and plastic maintenance.
Patent Information
- Application Number
- CN202411498740.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing solid-state regeneration process of aluminum alloy, the oxide film on the surface of aluminum chips hinders the metallurgical combination between chips and chips, affecting the mechanical properties of the material.
By plating copper plating on the surface of AA6063 aluminum dandruff, the impact of the oxide film is reduced, and combined with thermal squeeze and T6 thermal treatment process to generate high-performance AL-CU conformities.
It significantly improves the intensity of matrix alloy, while maintaining good plasticity, and the mechanical properties are close or better than native aluminum alloy.
Smart Images

Figure CN119372513A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum alloy production technology, specifically relating to a method for solid-state regeneration of Al-Cu based alloys using AA6063 aluminum scraps. Background Technology
[0002] Aluminum alloys, due to their advantages such as low density, high specific strength and stiffness, good machinability, and strong corrosion resistance, are widely used in the automotive, shipbuilding, and aerospace industries, becoming the second largest industrial metal in terms of usage after steel. Currently, aluminum alloys are the most widely used lightweight material in automobile manufacturing worldwide. Lightweighting automobiles effectively reduces fuel consumption and emissions. 6000 series aluminum alloys are heat-treatable wrought aluminum alloys with good weldability, excellent machinability, and moderate strength, making them widely used in the production of various automotive profiles. Every year, a huge amount of aluminum alloys are scrapped due to reaching the end of their service life. Compared to primary production, recycling and reprocessing scrap aluminum can save 90% of the energy consumed. Therefore, the recycling and utilization of scrap aluminum has gradually become a core issue in aluminum alloy industry research. Currently, there are two main methods for recycling scrap aluminum: one is the casting recycling method, which involves remelting to obtain recycled ingots; the other is the solid-state recycling method, which involves thermoplastic deformation to obtain recycled billets or aluminum materials. Recycled aluminum alloys largely retain their original alloy composition, achieving the mechanical properties of virgin aluminum alloys as much as possible. This method not only has significant economic benefits but is also energy-saving and environmentally friendly.
[0003] The casting recycling method suffers from significant material loss due to severe oxidation of aluminum scraps during heating, resulting in a yield rate generally below 90% and generating a large amount of alumina-containing byproducts (commonly known as aluminum ash). The recycling and reuse of these byproducts is quite difficult. Solid-state aluminum alloy recycling processes offer advantages such as low energy consumption and high yield, showing broad application prospects. However, because aluminum alloys are very prone to oxidation, forming an Al2O3 film on the surface, and alumina possesses high chemical stability, this film remains stable during aluminum scrap consolidation. It neither dissolves into the matrix nor reacts chemically with it. Al2O3 fragments and particles only break and spheroidize during the plastic deformation of the aluminum alloy, hindering atomic diffusion, affecting the quality of the metallurgical interface between aluminum scraps, and reducing the material's plasticity. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a method for generating an Al-Cu-based alloy by plating copper onto the surface of AA6063 aluminum chips, thereby mitigating the impact of the oxide film on the metallurgical bonding between chips during solid-state regeneration. This Al-Cu-based alloy allows the original interfacial phase to dissolve during subsequent heat treatment, while simultaneously diffusing Cu atoms into the aluminum alloy matrix, enhancing the strengthening effect of the precipitated phases, significantly improving the strength of the matrix alloy, and maintaining good ductility.
[0005] A method for solid-state regeneration of Al-Cu based alloys using AA6063 aluminum scrap specifically includes the following steps:
[0006] Step 1: Cleaning of recycled aluminum shavings
[0007] The recycled AA6063 aluminum shavings were soaked in a metal cleaning solution, rinsed with clean water, ultrasonically cleaned with alcohol, and then dried in a vacuum drying oven for later use.
[0008] Step 2: Preparation of electroless copper plating solution
[0009] A chemical copper plating solution was prepared according to the following ratio: CuSO4·5H2O solution with a concentration of 42–45 g / L, disodium ethylenediaminetetraacetate solution with a concentration of 42–45 g / L, NaOH solution with a concentration of 20–25 mg / L, K4[Fe(CN)6]·3H2O solution with a concentration of 20–25 mL / L, HCHO solution with a concentration of 100–110 mL / L, and CH3OH solution with a concentration of 100–110 mL / L.
[0010] Step 3: Copper plating of aluminum scraps
[0011] The AA6063 aluminum scraps obtained in step 1 are pretreated by soaking the aluminum scraps in 3% to 5% NaOH solution for 3 to 5 minutes, then soaking them in 50% to 60% HNO3 solution for 2 to 5 minutes to remove the surface oxide film. The pretreated aluminum scraps are then soaked in a chemical copper plating solution for copper plating, and then cleaned with deionized water and alcohol before being vacuum dried.
[0012] Step 4: Press into blanks
[0013] Under air conditions, copper-plated and dried aluminum shavings are placed into a steel mold cavity and subjected to multiple filling and pressing processes using a press under a pressure of 200–900 MPa. After the final pressing, the pressure is held for 5–10 minutes to obtain a relatively dense compact.
[0014] Step 5: Hot extrusion
[0015] Under a protective atmosphere, the compact is induction heated and held at a certain temperature, and then placed in an extrusion cylinder at a temperature of 400-450°C for hot extrusion to obtain recycled Al-Cu-based extruded bars.
[0016] Step 6: Heat treatment
[0017] Recycled Al-Cu-based extruded bars are subjected to T6 heat treatment to obtain T6-state recycled Al-Cu-based products with excellent comprehensive properties.
[0018] in:
[0019] In step 1, the AA6063 aluminum shavings are 5-20 mm in length, 1-5 mm in width, and 13-25 μm in thickness.
[0020] In step 3, 25-30g of aluminum shavings are added to every 500mL of copper plating solution, and the aluminum shavings must be cleaned with deionized water after each step before proceeding to the next step.
[0021] In step 3, the copper plating time is not less than 20 seconds, and the plating solution temperature is 60-70℃.
[0022] In step 4, the pressed blank is demolded by reverse ejection during the demolding process.
[0023] In step 5, the induction heating process is carried out under an inert protective gas with an oxygen concentration of <100ppm.
[0024] In step 5, the induction heating rate is 20-25℃ / min, and the temperature is heated to 450-500℃.
[0025] In step 5, the extrusion ratio is (9-25):1, and the relative density of the extruded bar is 95%-96%.
[0026] In step 6, the T6 heat treatment process is as follows: the extruded bar is solution treated at 450-530℃ for 1-6 hours, water quenched, and aged at 160-200℃ for 8-32 hours.
[0027] The key technical point of this invention is: using low-cost waste AA6063 aluminum scrap as raw material, through a process combining chemical copper plating on the surface of the aluminum scrap, hot extrusion of the scrap compact and T6 heat treatment, the interface between the original aluminum scrap is eliminated and an Al-Cu based alloy with significantly improved strength while maintaining good plasticity is obtained.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] (1) This invention uses recycled waste AA6063 aluminum alloy scraps as raw materials, and rapidly induction heats the aluminum alloy scraps in a protective gas atmosphere to prepare high-performance recycled aluminum alloy products, which reduces energy consumption and pollution, while achieving excellent mechanical properties.
[0030] (2) Short process: The process includes cleaning, drying, chemical plating, pressing, pressing heating and hot extrusion, and heat treatment.
[0031] (3) All solid-state, low energy consumption, low cost: This method does not melt aluminum alloy, thus avoiding the energy input required to melt aluminum alloy, preventing metal loss and alumina inclusions caused by the rapid reaction of highly active liquid metal with air, simplifying the recycling process, having no impact on the environment, and reducing costs.
[0032] (4) Good mechanical properties of materials: The materials produced by this process have high strength and relatively good plasticity, and their mechanical properties are comparable to or better than those of materials prepared by hot extrusion of the corresponding primary aluminum alloy.
[0033] (5) The process of the present invention can transform the low-strength 6-series aluminum alloy into the high-strength 2-series aluminum alloy, and greatly improve the mechanical properties of the material while recycling the aluminum alloy. Attached Figure Description
[0034] Figure 1 In Example 1 and Comparative Example 1 of this invention, SEM images of solid recycled Al-Cu-based products before and after heat treatment, and SEM images of solid recycled AA6063 aluminum scrap samples before and after heat treatment are shown. Among them, Figure (a) is the SEM image of the recycled aluminum alloy product of Comparative Example 1, Figure (b) is the SEM image of the T6 state recycled aluminum alloy product of Comparative Example 1, Figure (c) is the SEM image of the recycled Al-Cu-based alloy product of Example 1, and Figure (d) is the SEM image of the T6 state solid recycled Al-Cu-based product of Example 1.
[0035] Figure 2 In Example 1 and Comparative Example 1 of this invention, XRD patterns of solid recycled Al-Cu-based products before and after heat treatment and solid recycled AA6063 aluminum scrap products before and after heat treatment are shown. Among them, Figure (a) is the XRD pattern of recycled aluminum alloy products and T6 state recycled aluminum alloy products in Comparative Example 1, and Figure (b) is the XRD pattern of recycled Al-Cu-based alloy products and T6 state solid recycled Al-Cu-based products in Example 1.
[0036] Figure 3 In Example 1 and Comparative Example 1 of this invention, EBSD images of solid recycled Al-Cu-based products before and after heat treatment and solid recycled AA6063 aluminum scrap products before and after heat treatment are shown. Among them, Figure (a) is the IPF image of the recycled aluminum alloy product of Comparative Example 1, Figure (b) is the IPF image of the T6 state recycled aluminum alloy product of Comparative Example 1, Figure (c) is the IPF image of the recycled Al-Cu-based alloy product of Example 1, Figure (d) is the phase distribution diagram of the recycled Al-Cu-based alloy product of Example 1, Figure (e) is the IPF image of the T6 state solid recycled Al-Cu-based product of Example 1, and Figure (f) is the phase distribution diagram of the T6 state solid recycled Al-Cu-based product of Example 1.
[0037] Figure 4In Example 1 and Comparative Example 1 of this invention, the engineering stress-strain curves of solid recycled Al-Cu-based products and recycled aluminum alloy products before and after heat treatment are shown; wherein, Figure (a) is the engineering stress-strain curve of the recycled aluminum alloy product of Comparative Example 1 before and after heat treatment, and Figure (b) is the engineering stress-strain curve of the recycled Al-Cu-based alloy product of Example 1 before and after heat treatment.
[0038] Figure 5 In Example 2 of this invention, SEM images of solid-state regenerated Al-Cu-based samples before and after heat treatment are shown; wherein, Figure (a) is a SEM image of the regenerated Al-Cu-based alloy product, and Figure (b) is a SEM image of the T6 state solid-state regenerated Al-Cu-based aluminum alloy product.
[0039] Figure 6 In Example 2 of this invention, XRD patterns of solid-state recycled Al-Cu-based products before and after heat treatment;
[0040] Figure 7 In Embodiment 2 of the present invention, EBSD microstructure diagrams of solid-state recycled Al-Cu-based products before and after heat treatment are shown; wherein, Figure (a) is the IPF diagram of the solid-state recycled Al-Cu-based product, Figure (b) is the phase distribution diagram of the solid-state recycled Al-Cu-based product, Figure (c) is the IPF diagram of the T6 state solid-state recycled Al-Cu-based aluminum alloy product, and Figure (d) is the phase distribution diagram of the T6 state solid-state recycled Al-Cu-based aluminum alloy product.
[0041] Figure 8 In Example 2 of this invention, the engineering stress-strain curves of the solid-state regenerated Al-Cu-based sample before and after T6 heat treatment are shown. Detailed Implementation
[0042] Example 1
[0043] In this embodiment, the AA6063 aluminum shavings used have the following dimensions: length 5-20mm, width 1mm, and thickness 13-18μm.
[0044] A method for solid-state regeneration of Al-Cu based alloys using AA6063 aluminum scrap specifically includes the following steps:
[0045] Step 1: Cleaning of recycled aluminum shavings
[0046] Weigh 300g of recycled AA6063 aluminum shavings, soak them in a metal cleaning solution, rinse them with clean water, ultrasonically clean them with alcohol for 20 minutes, and then dry them in a vacuum drying oven at 170℃ for 20 minutes to remove moisture for later use.
[0047] Step 2: Preparation of electroless copper plating solution
[0048] A 6L electroless copper plating solution was prepared according to the following ratio: 42g / L CuSO4·5H2O solution, 42g / L disodium ethylenediaminetetraacetate solution, 20g / L NaOH solution, 20mg / L K4[Fe(CN)6]·3H2O stabilizer solution, 24mL / L HCHO reducing agent solution, and 100mL / L CH3OH solution.
[0049] Step 3: Copper plating of aluminum scraps
[0050] The AA6063 aluminum shavings obtained in step 1 were divided into 25g portions and pretreated: each portion of aluminum shavings was soaked in 5% NaOH for 5 minutes, rinsed with deionized water, and then soaked in 50% HNO3 solution for 2 minutes to remove the surface oxide film. After rinsing with deionized water, the pretreated aluminum shavings were obtained.
[0051] Each batch of pretreated aluminum shavings was immersed in 500mL of electroless copper plating solution for 30 seconds for copper plating at a temperature of 60℃. After being cleaned with deionized water and alcohol, it was placed in a vacuum drying oven at 170℃ and vacuum dried for 120 minutes.
[0052] Step 4: Press into blanks
[0053] Under air conditions, copper-plated and dried aluminum shavings are placed into a cylindrical steel mold cavity with a diameter of 53mm coated with graphite lubricant. Using a 200t press, the mold is pre-pressed four times at a pressing pressure of 200MPa. During the pre-pressing process, the mold is filled and pressed multiple times. Finally, the mold is pressed at a pressing pressure of 800MPa and held for 5 minutes. Then, the pressed blank is demolded in the reverse direction by ejecting it from the lower mold, thus obtaining a blank with a diameter of 53mm and a height of 60mm. The relative density of the blank is 98.7%.
[0054] Step 5: Hot extrusion
[0055] The forming press glove box is evacuated to a vacuum level below 0.01 MPa. High-purity argon gas is then introduced to reduce the oxygen content to less than 100 ppm. A medium-frequency induction heating device is used to rapidly heat the fragmented compact at a rate of 20°C / min, raising the temperature to 450°C in 20 minutes and holding it for 5 minutes to obtain the heated compact. The heated compact is then quickly transferred to a 400°C, 57mm diameter upsetting die. Using a 200t press at a pressure of 800 MPa, hot extrusion is performed using a square extrusion nozzle with an extrusion ratio of 25:1 to obtain an aluminum alloy extruded bar. The extruded bar has a relative density of 96%, which is a recycled Al-Cu based alloy product.
[0056] The SEM microstructure of the recycled Al-Cu based alloy product obtained in step 5 is shown below. Figure 1As shown in (c), the atomic percentage of Cu in region ③ is 0.35%, and the atomic percentage of Cu in point ④ is 25.88%. The IPF diagram of the recycled Al-Cu based alloy is shown below. Figure 3 As shown in (c), the phase distribution diagram is as follows: Figure 3 As shown in (d).
[0057] Step 6: Heat treatment
[0058] The recycled Al-Cu based alloy products were placed in a muffle furnace for T6 heat treatment: solution treatment at 500℃ for 2 hours; water quenching and artificial aging at 170℃ for 16 hours, to obtain T6 state solid recycled Al-Cu based products with excellent comprehensive properties such as strength and hardness.
[0059] The SEM microstructure of the T6 state solid-state regenerated Al-Cu-based product obtained in step 6 is shown below. Figure 1 As shown in (d), the atomic percentage of Cu in region ⑤ is 1.89%, and the atomic percentage of Cu in point ⑥ is 19.70%; the IPF diagram of the T6 state solid-state regenerated Al-Cu-based product is shown below. Figure 3 As shown in (e), the phase distribution diagram is as follows: Figure 3 As shown in (f).
[0060] XRD patterns of solid-state recycled Al-Cu-based products before and after heat treatment are shown below. Figure 2 As shown in (b), the engineering stress-strain curve is as follows: Figure 4 As shown in (b).
[0061] Results: The 4.68Cu solid-state regenerated Al-Cu-based sample prepared at 450℃ under argon protection achieved a yield strength of 361MPa, a tensile strength of 417MPa, and an elongation of 11.6% after T6 heat treatment.
[0062] Example 2
[0063] In this embodiment, the AA6063 aluminum shavings used have the following dimensions: length 5-20mm, width 1mm, and thickness 13-18μm.
[0064] A method for solid-state regeneration of Al-Cu based alloys using AA6063 aluminum scrap specifically includes the following steps:
[0065] Step 1: Cleaning of recycled aluminum shavings
[0066] Weigh 300g of recycled AA6063 aluminum shavings, soak them in a metal cleaning solution, rinse them with clean water, ultrasonically clean them with alcohol for 20 minutes, and then dry them in a vacuum drying oven at 170℃ for 20 minutes to remove moisture for later use.
[0067] Step 2: Preparation of electroless copper plating solution
[0068] A 6L electroless copper plating solution was prepared according to the following ratio: CuSO4·5H2O solution (42 g / L), disodium ethylenediaminetetraacetate solution (42 g / L), NaOH solution (20 g / L), K4[Fe(CN)6]·3H2O stabilizer solution (20 mg / L), HCHO reducing agent solution (24 mL / L), and CH3OH solution (100 mL / L).
[0069] Step 3: Copper plating of aluminum scraps
[0070] The AA6063 aluminum scraps obtained in step 1 were divided into 25g portions and pretreated: each portion of aluminum scraps was soaked in 5% NaOH for 5 minutes, rinsed with deionized water, and then soaked in 50% HNO3 solution for 2 minutes to remove the surface oxide film. After rinsing with deionized water, the pretreated aluminum scraps were obtained.
[0071] Each batch of pretreated aluminum shavings was immersed in 500mL of electroless copper plating solution for 3 minutes for copper plating at a temperature of 60℃. After being cleaned with deionized water and alcohol, it was placed in a vacuum drying oven at 170℃ and vacuum dried for 120 minutes.
[0072] Step 4: Press into blanks
[0073] Under air conditions, copper-plated and dried aluminum shavings are placed into a cylindrical steel mold cavity with a diameter of 53mm coated with graphite lubricant. Using a 200t press, the mold is pre-pressed four times at a pressing pressure of 200MPa. During the pre-pressing process, the mold is filled and pressed multiple times. Finally, the mold is pressed at a pressing pressure of 800MPa and held for 5 minutes. Then, the pressed blank is demolded in the reverse direction by ejecting it from the lower mold, thus obtaining a blank with a diameter of 53mm and a height of 60mm. The relative density of the blank is 98.7%.
[0074] Step 5: Hot extrusion
[0075] The forming press glove box is evacuated to a vacuum level below 0.01 MPa. High-purity argon gas is then introduced to reduce the oxygen content to less than 100 ppm. A medium-frequency induction heating device is used to rapidly heat the fragmented compact at a rate of 20°C / min, raising the temperature to 480°C in 25 minutes and holding it for 5 minutes to obtain the heated compact. The heated compact is then quickly transferred to a 400°C, 57mm diameter upsetting die. Using a 200t press at a pressure of 800 MPa, hot extrusion is performed using a square extrusion nozzle with an extrusion ratio of 25:1 to obtain an aluminum alloy extruded bar. The extruded bar has a relative density of 95.7%, which is a recycled Al-Cu based alloy product.
[0076] SEM microstructure of solid-state regenerated Al-Cu-based products is shown below. Figure 5 As shown in (a), the atomic percentage of Cu in region ① is 0.38%, and the atomic percentage of Cu in point ② is 33.37%. The IPF diagram of the solid-state recycled Al-Cu-based product is shown below. Figure 7 As shown in (a), the phase distribution diagram is as follows: Figure 7 As shown in (b).
[0077] Step 6: Heat treatment
[0078] The recycled Al-Cu based alloy products were placed in a muffle furnace for T6 heat treatment: solution treatment at 500℃ for 2 hours; water quenching and artificial aging at 170℃ for 16 hours, to obtain T6 state solid recycled Al-Cu based aluminum alloy products with excellent comprehensive properties such as strength and hardness.
[0079] SEM microstructure of T6 state solid-state recycled Al-Cu based aluminum alloy products is shown below. Figure 5 As shown in (b), the atomic percentage of Cu in region ③ is 2.31%, and the atomic percentage of Cu in point ④ is 28.01%. The IPF diagram of the T6 state solid-state recycled Al-Cu based aluminum alloy product is shown below. Figure 7 As shown in (c), the phase distribution diagram is as follows: Figure 7 As shown in (d).
[0080] XRD patterns of solid-state recycled Al-Cu-based products before and after heat treatment are shown below. Figure 6 As shown, the engineering stress-strain curve is as follows: Figure 8 As shown.
[0081] Results: The 6.18Cu solid-state regenerated Al-Cu-based sample prepared at 480℃ under argon protection atmosphere achieved a yield strength of 388MPa, a tensile strength of 421MPa, and an elongation of 6.7% after T6 heat treatment.
[0082] Comparative Example 1
[0083] In this embodiment, the AA6063 aluminum shavings used have the following dimensions: length 5-20mm, width 1mm, and thickness 13-18μm.
[0084] A method for solid-state recycling of aluminum alloys using AA6063 aluminum scraps specifically includes the following steps:
[0085] Step 1: Cleaning of recycled aluminum shavings
[0086] Weigh 300g of recycled AA6063 aluminum shavings, soak them in a metal cleaning solution, rinse them with clean water, ultrasonically clean them with alcohol for 20 minutes, and then dry them in a vacuum drying oven at 170℃ for 20 minutes to remove moisture for later use.
[0087] Step 2: Press into blanks
[0088] Under air conditions, dried aluminum shavings are placed into a cylindrical steel mold cavity with a diameter of 53mm coated with graphite lubricant. Using a 200t press, the shavings are pre-pressed four times at a pressing pressure of 200MPa. During the pre-pressing process, the shavings are filled and pressed multiple times. Finally, after pressing at a pressing pressure of 800MPa, the pressure is held for 5 minutes. Then, the pressed blank is demolded in the reverse direction by ejecting it from the lower mold, thus obtaining a blank with a diameter of 53mm and a height of 60mm. The relative density of the blank is 98.7%.
[0089] Step 3: Hot extrusion
[0090] The forming press glove box is evacuated to a vacuum level below 0.01 MPa. High-purity argon gas is then introduced to reduce the oxygen content to less than 100 ppm. A medium-frequency induction heating device is used to rapidly heat the fragmented compact at a rate of 20°C / min, raising the temperature to 450°C in 20 minutes and holding it for 5 minutes to obtain the heated compact. The heated compact is then quickly transferred to a 400°C, 57mm diameter upsetting die. Using a 200t press at a pressure of 800 MPa, hot extrusion is performed using a square extrusion nozzle with an extrusion ratio of 25:1 to obtain an aluminum alloy extruded bar. The relative density of the extruded bar is 95.8%, which is the recycled aluminum alloy product.
[0091] The SEM microstructure of the recycled aluminum alloy product obtained in step 3 is shown below. Figure 1 As shown in (a), the atomic percentage of Cu in region ① is 0.05%; the IPF diagram of the recycled aluminum alloy product is shown below. Figure 3 As shown in (a).
[0092] Step 4: Heat treatment
[0093] The recycled aluminum alloy products were placed in a muffle furnace for T6 heat treatment: solution treatment at 530℃ for 1 hour; water quenching and artificial aging at 170℃ for 8 hours, resulting in T6 recycled aluminum alloy products with excellent comprehensive properties such as strength and hardness.
[0094] The SEM microstructure of the T6-state recycled aluminum alloy product obtained in step 4 is shown below. Figure 1 As shown in (b), the atomic percentage of Cu in region ② is 0.04%; the IPF diagram of the T6 state recycled aluminum alloy product is shown below. Figure 3 As shown in (b).
[0095] XRD patterns of recycled aluminum alloy products before and after heat treatment are shown below. Figure 2 As shown in (a), the engineering stress-strain curve is as follows: Figure 4 As shown in (a).
[0096] Results: The AA6063 recycled aluminum alloy sample prepared at 450℃ under argon protection atmosphere achieved a yield strength of 177MPa, a tensile strength of 218MPa, and an elongation of 18.2% after T6 heat treatment.
[0097] Figure 1 The chemical composition analysis of each region is shown in Table 1. The mechanical properties of the solid recycled Al-Cu-based product in Example 1 before and after heat treatment and the recycled aluminum alloy product in Comparative Example 1 before and after heat treatment are shown in Table 2. Figure 5 The chemical composition analysis of each region is shown in Table 3, and the mechanical properties of the solid recycled Al-Cu-based product in Example 1 before and after heat treatment are shown in Table 4.
[0098] Table 1 Figure 1 Chemical composition analysis (at.%) of different regions in China
[0099]
[0100] Table 2 Mechanical properties of solid recycled Al-Cu-based products before and after heat treatment in Example 1 and Comparative Example 1 recycled aluminum alloy products before and after heat treatment.
[0101]
[0102] Table 3 Figure 5 Chemical composition analysis (at.%) of different regions in China
[0103]
[0104] Table 4 Mechanical properties of solid recycled Al-Cu-based products before and after heat treatment in Example 2
[0105]
Claims
1. A method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips, characterized in that: The specific steps include: Step 1: Cleaning of recycled aluminum chips The recovered AA6063 aluminum chips are soaked in a metal cleaning solution, cleaned with clean water, ultrasonically cleaned with alcohol, and then dried in a vacuum drying oven for later use; Step 2: Preparation of chemical copper plating solution Prepare a chemical copper plating solution according to the ratio of 42-45 g / L CuSO4·5H2O solution, 42-45 g / L disodium ethylenediaminetetraacetic acid solution, 20-25 g / L NaOH solution, 20-25 mg / L K4[Fe(CN)6]·3H2O solution, 20-25 mL / L HCHO solution and 100-110 mL / L CH3OH solution; Step 3: Copper plating of aluminum chips The AA6063 aluminum chips obtained in step 1 are pretreated: the aluminum chips are soaked in 3% to 5% NaOH for 3 to 5 minutes, and then soaked in 50% to 60% HNO3 solution for 2 to 5 minutes to remove the surface oxide film, and the pretreated aluminum chips are soaked in a chemical copper plating solution for copper plating, and then vacuum dried after cleaning with deionized water and alcohol; Step 4: Pressing into a blank Under air conditions, the copper-plated and dried aluminum chips are placed in a steel mold cavity, and a press is used to perform multiple filling and pressing at a pressure of 200 to 900 MPa. After the last pressing, the pressure is maintained for 5 to 10 minutes to obtain a relatively dense green compact. Step 5: Hot Extrusion Under a protective atmosphere, the pressed green body is induction heated and kept warm, and then placed in an extrusion barrel at a temperature of 400-450°C for hot extrusion to obtain a recycled Al-Cu based extruded rod; Step 6: Heat Treatment The recycled Al-Cu based extruded rods are subjected to T6 heat treatment to obtain T6 state recycled Al-Cu based products with excellent comprehensive properties.
2. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In the step 1, the size of the AA6063 aluminum chips is 5 to 20 mm in length, 1 to 5 mm in width, and 13 to 25 μm in thickness.
3. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In step 3, 25 to 30 g of aluminum chips are added to every 500 mL of copper plating solution, and after each step of this step, the aluminum chips are cleaned with deionized water before proceeding to the next step.
4. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In step 3, the copper plating time is not less than 20 seconds, and the plating solution temperature is 60-70°C.
5. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In the step 4, the green compact is demolded by reverse ejection during demolding.
6. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In step 5, the induction heating process is carried out under an inert protective gas, and the oxygen concentration in the inert protective gas is less than 100 ppm.
7. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In step 5, the heating rate of induction heating is 20-25°C / min, and the heating temperature is 450-500°C.
8. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In the step 5, the extrusion ratio is (9-25):1, and the relative density of the extruded rod is 95%-96%.
9. The method for solid-state regeneration of Al-Cu based alloy using AA6063 aluminum chips according to claim 1, characterized in that: In step 6, the T6 heat treatment process is: solution treatment of the extruded rod at 450-530° C. for 1-6 hours, water quenching, and aging at 160-200° C. for 8-32 hours.
Citation Information
Cited By
Preparation method of 6-series aluminum alloy solid recovery extruded profile and automotive extruded profile
CN122462522A